A napi ingázás kérdésköre a kilencvenes években Magyarországon - Szabó, Pál (Tér és Társadalom, 1998)
In the nineties the idea of the commuting is disappearing from the mind of the hungarian society. The examination of its attributes is a rare topic in scientific researches and it falls into the background in the interest of sectorial politics nowadays in Hungary. These facts are causeless because the newest data (1996) shows that 25 per cent of occupied population is commuter just as in 1990. The statistical definition of commuting is criticized sometimes, but it is widely conceded with some mistakes, so the arising opinions do not cause serious dilemmas. In the formation of commuting objective and subjective factors participate, but during the historical development most of them altered. The earlier growth tendency has changed since 1980 in Hungary: the number of occupied population and of the commuters decreased. In spite of this decrease the rate of the commuters grew between 1980 and 1990, and the index has stagnated since 1990. The explanation of it is a collective effect of more social and economical factors. It is an interesting fact that the high rate of commuting does not cause high rate of unemployment in most of settlements. It is interesting also that the contact of the city status and the attraction of labour weakened in the previous years. These are reinforced by statistical datas. In nineties a lot of new social and economical factors affect the commuting in Hungary. In addition to the decisions of sectorial politics affect the commuting too. These are collected in the second part of this study.